Closure - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2020)
Scope of JIFAM PaperJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited to the following.-          I & F Function-          I & F Demand - Supply-          I & F User Behavior-          I & F Evaluation-          I & F Policy-          I & F Preliminary Idea-          I & F Planning-          I & F Design-          I & F Construction-          I & F Administration Aspects-          I & F Technical Certification-          I & F Information System-          I & F Operation System-          I & F Maintenance System-          I & F Disposal-          I & F Economics & Financial Aspect-          I & F Spatial & Environmental Aspect-          I & F Sustainability Aspects-          I & F Strategic Aspect-          Decision Making for I&FAM-          Statistics for I&FAM-          Mathematics for I&FAM-          Operation Research for I&FAM-          I & F Managing Organisation Aspect